2013
DOI: 10.1002/jrs.4189
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chlorine substitution on triplet state structure of thioxanthone: A time‐resolved resonance Raman study

Abstract: Substitution plays an important role in determining the triplet state reactivity. In this paper, we have studied the effect of chlorine substitution on the triplet state structure and the reactivity of thioxanthone (TX). We have employed time‐resolved resonance Raman technique to understand the structure of the lowest triplet excited state of 2‐chlorothioxanthone (CTX). The experimental findings have been corroborated with the computational results using density functional theory. Akin to the parent compound (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Pandey and coworkers used time‐resolved resonance Raman to study the effect of chlorine substitution on the triplet state structure of thioxanthone (TX). To accomplish this, the authors employed TRRR to understand the structure of the lowest triplet excited state of 2‐chlorothioxanthone (CTX) . Reigue et al .…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Pandey and coworkers used time‐resolved resonance Raman to study the effect of chlorine substitution on the triplet state structure of thioxanthone (TX). To accomplish this, the authors employed TRRR to understand the structure of the lowest triplet excited state of 2‐chlorothioxanthone (CTX) . Reigue et al .…”
Section: Introductionmentioning
confidence: 84%
“…To accomplish this, the authors employed TRRR to understand the structure of the lowest triplet excited state of 2-chlorothioxanthone (CTX). [165] Reigue et al reported CW measurements of resonance Raman profiles, line-widths, and cross sections of fluorescent dyes with application to Nile Blue A in water and ethanol. This study demonstrates the possibility of routine RRS measurements using standard Raman spectrometers, as opposed to more complicated time-resolved techniques.…”
Section: Coherent Anti-stokes Raman Spectroscopymentioning
confidence: 99%
“…This enables Raman spectroscopy a highly specific probe providing unique chemical fingerprinting information. In other words two different molecules have two different Raman spectra; even an atomic substitution is known to affect the Raman spectrum of the parent molecule (13). The high specificity of the technique could be understood with the fact that same molecule in the different chemical environments (14) and even two polymorphic forms have different Raman signatures.…”
Section: Raman Spectroscopy-based Approachesmentioning
confidence: 99%
“…In this work, conventional Raman and time‐resolved resonance Raman spectroscopy (TR 3 ) techniques were used to examine the ground and the triplet excited states structure, respectively. TR 3 spectroscopy is a powerful technique to elucidate the vibrational structure of the transient species . When the Raman excitation wavelength is in resonance with an allowed electronic transition of the molecule, the Raman peaks coupled to the chromophore become enhanced, accounting for the high sensitivity and selectivity of the technique .…”
Section: Introductionmentioning
confidence: 99%
“…TR 3 spectroscopy is a powerful technique to elucidate the vibrational structure of the transient species. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] When the Raman excitation wavelength is in resonance with an allowed electronic transition of the molecule, the Raman peaks coupled to the chromophore become enhanced, accounting for the high sensitivity and selectivity of the technique. [49][50][51][52][53][54] Resonance Raman spectroscopy generally involves measurement of the Raman intensities of different modes as a function of wavelength, known as Raman excitation profiles (REPs).…”
Section: Introductionmentioning
confidence: 99%